Morphology and Formation of Glassy Volcanic Ash from the August 12-15, 1991 Eruption of Hudson Volcano, Chile - Scasso, Roberto Adrian (2005)
The 1991 explosive eruption of Hudson volcano in Chile ejected about 2.7 km3 (DRE) of basalt and trachyandesite magma as tephra fall. A majority of the fallout occurred from an eruption during the period August 12-15, 1991, producing an extensive deposit to the east of the volcano in Chile and Argentina. Dacitic, glassy tephra from this phase of the eruption exhibit a remarkable variety in particle morphology and color, ranging from dark, poorly-vesicular shards to light-colored, pipe-vesicular micropumice. Fractal analysis of glassy particle outlines shows that at least four distinct types can be discriminated: blocky, poorly-vesicular, highly vesicular with spherical vesicles, and pipe vesicular. A quantitative comparison of particle morphologies using principal component analysis of fractal spectrums of the Hudson tephra with other tephra produced by eruptions with known fragmentation mechanisms, together with SEM imaging of particle surfaces, indicates that production of the Hudson tephra involved both interaction with external water and exsolution of dissolved volatiles. Blocky particles likely represent magma that was fragmented by magma-water interactions before exsolution of all dissolved volatiles could occur. The great diversity of particle types in the August 12-15, 1991 Hudson tephra fall can be attributed to eruption of volatile-rich trachyandesite magma through an ice-filled caldera where subglacial melting led to a supply of external water that interacted intermittently with the discharge of magma driven primarily by volatile exsolution.